Tensile Properties of Rubberized Concrete Containing High Volume Fly Ash - Murali, Mugineysh (Universiti Teknologi PETRONAS, 2021)
The exponential growth of automobile industry has led to the rise in waste tyre generation due to their inability to degrade in their natural condition. Waste tyres disposed of in landfills cause serious health and environmental issues by rapid accumulation of useful land and provision of breeding place for mosquitoes and vermin. These challenges subsequently brought the idea of incorporating the waste tyres in form of crumb rubber (CR) in concrete and other cementitious composites, which has proven to be an effective method to dispose of the waste tyres. Similarly, a lot of fly ash (FA) is being generated as a waste material from coal combustion process at power generating plants. To solve the problem of this waste accumulation and pollution, it is being used as a cement substitute in cement composites due to it pozzolanic properties. Although these two waste materials (CR and FA) have been used separately in concrete, very little work exist on their use together in high volume for concrete production.